Imatinib and beyond: targeting activated tyrosine kinases in myeloproliferative disorders - Hochhaus, Andreas; Reiter, Andreas (Onkologie, 2012)
Tyrosine kinases (TKs) play a major role in cellular signal transduction. Deregulated TK activity has been observed in solid cancers and hematologic malignancies. Advances in the understanding of the oncogenic activation of TKs led to the identification of new kinase inhibitors with improved potency, specificity, and efficacy. With the advent of imatinib mesylate, a new era in the management of patients with BCR-ABL+ chronic myelogenous leukemia (CML), gastrointestinal stromal tumors, and myeloproliferative neoplasms including chronic myelomonocytic leukemia with PDGFRB gene rearrangements and hypereosinophilic syndrome has begun. CML represents a model for the rational design of TK inhibitors based on the insights into signal transduction pathways. In CML, treatment with imatinib led to an outstanding clinical efficacy with limited toxicity. In BCR-ABL-negative myeloproliferation, the finding of activating point mutations in JAK2 prompted the development of JAK inhibitors to target this activated pathway. Aberrations of epigenetically active genes are the latest finding in the pathogenesis of myeloproliferative disorders and will serve as another target for innovative therapies.
Gesehen am 30.10.2018